Peningkatan Hasil Belajar Kognitif Calon Guru Menggunakan Strategi RQA (Reading, Questioning and Answering) - Yunus, Muh Rizal Kurniawan (Universitas Sulawesi Barat, 2024)
This study aims to enhance students’ cognitive learning outcomes through the implementation of the Reading, Questioning, Answering (RQA) strategy. A Classroom Action Research approach was employed using the Kemmis and Taggart model, comprising two cycles. The research participants were students from the Biology Education Program at the University of Sulawesi Barat, enrolled in the Educational Profession course. Data on students’ cognitive learning outcomes were collected using test instruments in the form of multiple-choice and essay questions related to the course material. The findings revealed that in Cycle 1, the average N-gain score for students' cognitive learning outcomes was categorized as low. After refining the strategy in Cycle 2, the N-gain scores improved to a medium category. Improvements included providing key points as guidance during the Reading phase and utilizing a question framework based on Bloom’s taxonomy during the Questioning phase. The adjusted implementation of the RQA strategy significantly enhanced students’ understanding and learning outcomes compared to conventional teaching methods. This research demonstrates that the RQA strategy is not only effective in improving cognitive learning outcomes but also fosters active student engagement in the learning process. These findings suggest that incorporating activity-based learning strategies such as RQA can serve as an effective alternative to improve the quality of higher education instruction